Panduan Pengukuran Halal Lifestyle: Pedoman Literasi Keuangan Syariah dan Literasi Halal: Halal Lifestyle Measurement Guide: Guidelines for Islamic Financial Literacy and Halal Literacy - Irmadatus Sholekhah; Dibyo Waskito Guntoro (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
All these aspects of life are actually inseparable in the routine activities of a Muslim; that is called the halal lifestyle. The term